EKSPLORASI ETNOMATEMATIKA PADA RUMAH ADAT JOGLO DI KELURAHAN JAGALAN, BANGUNTAPAN BANTUL - Lestari, Endang Dwi; Suhendri, Huri; Alamsyah, Mashudi (LPPM Universitas Bina Bangsa, 2024)
This research aims to identify and describe the mathematical concepts contained in the Joglo Traditional House in Jagalan sub-district (Omah UGM). The research method used is ethnomathematics with the research object being the Joglo Traditional House. Source of research data: research object, namely the Joglo traditional house, three sources consisting of: two managers and one elder, and related documents discussing the Joglo traditional house. Data collection techniques used: observation, interviews, and documentation. Research instruments used: observation guide, interview guide, and document study guide. Based on the research results obtained and data analysis, it was concluded that in the Joglo Traditional House there are mathematical concepts, namely: spatial shapes, flat shapes, lines, angles and geometric transformations